ANALISIS PENDAPATAN USAHATANI KOPI (Coffea sp) RAKYAT DI KECAMATAN LIMBANGAN KABUPATEN KENDAL - Agus Supriyadi; Sri Wahyuningsih; Shofia Nur Awami (MEDIAGRO, 2014)
Plantation agriculture is one sector that developed in Indonesia. One crop that a commodity is coffee. Limbangan District is one coffee producer in Kendal Regency.  The research was done to study the level of coffee farmer’s income and to study the factors that influence the coffee farmers income in Limbangan District Kendal Regency. Study using Stratified random sampling method. The results from data processing coffee farmers income each season (one year) is Rp. 4.660.636,67. A income acquiring from revenue less total cost, the mean cost are fixed cost (tax and decrise equipment) and variabel cost (labour and fertilizer cost). Simultaneous testing at significance level (α) = 5% indicates that the land area, production, costs of production, and education significant effect on the coffee farmers income in Limbangan District Kendal Regency. The effect of four variables on coffee farmers income indicated with R Square = 0.933,  which means that income influenced by land area, labor, cost of production, production, experience, age, and education are 93.3 percent and 6.7 percent are affected by other variables not included in the model. The t-test results of the variable land area, production, costs of production, and education partially significant effect on the coffee farmers income in Limbangan District Kendal Regency. A farmer expected be maximal a factors obvious influential in order that income increasing.   Keywords: Coffea, costs, income, land area, production.